Unexpected diversity of whitefly predators in Eocene Baltic amber—new fossil Serangium species (Coleoptera: Coccinellidae) - Szawaryn, Karol (Zootaxa, 2019)
Serangium is a tropical genus of minute ladybird beetles, which has been recently discovered in Baltic amber. Discovery of the third species, S. kalandyki sp. nov., demonstrates the surprising diversity of this group in the palaeoenvironment of Eocene ‘amber forests’. The new species, together with two previously described, form a well defined morphological group which suggests they all belong to a single lineage. An updated key to the fossil species of Serangium is presented. The diversity of the genus and its ecological affinities are discussed.